Algeria : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Algeria. (IMF Staff Country Reports; Country Report ;, 2008)
Algeria's external position has strengthened. Algeria's encouraging economic performances in recent years, reflecting market-oriented reforms and prudent macroeconomic policies in a favorable external environment, are discussed. The main challenges faced by Algeria are to ensure sustained high productivity and nonhydrocarbon growth and to lower further the still-high unemployment. In this context, Executive Directors' welcomed the recent increase in the reserve requirement rate. Gradual steps to reduce exemptions, improve VAT design, and eliminate the turnover tax would contribute importantly to improving the business climate.